Latihan Brain Gym untuk Peningkatan Kemampuan Memori Jangka Pendek pada Anak Sekolah Dasar di SD Negeri 43 Kota Pekanbaru - Fatma Nadia; Rika Mianna; Rahmaniza Rahmaniza; Heni Heri Yeni (Universitas Mathla'ul Anwar Banten, 2022)
BRAIN GYM TRAINING FOR IMPROVING SHORT TERM MEMORY ABILITY IN ELEMENTARY SCHOOL CHILDREN AT SD NEGERI 43 PEKANBARU CITY. Brain Gym is a new method developed to stimulate (lateral dimension), relieve (focusing dimension) or relax (focusing dimension) children who are involved in a learning situation that can stimulate children's short-term memory. Previously, SD Negeri 43 Pekanbaru had never received training and counseling related to Brain Gym. Activities carried out on site with counseling and training for elementary school children in grade IV that have been determined. The method used is the lecture method and practice. Counseling involves the homeroom teacher and all students in grade IV. The activity of asking permission from the principal and class teacher, determining the schedule for implementing activities, preparing things needed in implementation, conducting counseling related to Brain Gym theory and practice directly to all students. Previously, the activity was carried out with a pre test and after the activity a post test was carried out. The questionnaire uses the Short Portable Mental Status Questionnaire (PSMSQ). The counseling activity was carried out in 4 stages, namely initial survey, pre-test, Brain Gym counseling, brain gym practice, post-test and evaluation. Brain gym is done to improve short-term memory in school children. The total number of extension participants was 57 students and 3 teachers. The solution offered is by conducting counseling and practicing brain gym exercises which are expected to improve short-term memory in children at SD Negeri 43 Pekanbaru. The results of the pre-test mean value of 1.089 and post-test of 0.91 so that there was a significant change between the pretest and post-test, meaning that brain gym training can improve short-term memory of elementary school children.